MALAPRAKTIK DALAM TINDAK TUTUR KESEHATAN: KAJIAN PERSPEKTIF KOMUNIKASI ANTARA DOKTER DENGAN PASIEN - Siska Armawati Sufa; Didik Sugeng Widiarto (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2018)
Health communication has been defined as referring to any type of human communication whose content is concerned with health (Roger, 1996). This study describe about health communication, especially communication between physicians and hospitals as medical providers with their patients, and examines descriptively about how the communication between the doctors of RSUD Sultan Imanuddin Pangkalan Bun to the families of victims, Zacky as a patient. This research uses qualitative approach with the findings of data from interviews. The results conclude that the alleged malpractice case in Zacky's as a victim at RSUD Sultan Imanuddin Pangkalan Bun, is a manifestation of paternalistic model is the most dominant in past time used in health communication between physicians and patients that positioning is dominated by physicians, in this case who put the Zacky family as a passive object who submit all health and safety affairs to medical team. By contrast, the most useful model for healing a patient that the physician should adhere to is the Shared Model, which puts patients as subjects with socio-cultural background, values, hopes, feelings, desires, worries, and also crave for happiness and even save their lives from medical treatment. By using Shared Treatment Decision Making between the physicians and the patients regarding the medical action to be taken, accordingly the story about malpractice would not exist in the history of medicine in Indonesia would.